An indicator that measure argentinean smes value migration - Casella Volosin, Guido (Ediciones UNL. Secretaría de Extensión de la UNL, 2022)
This research sought to construct an indicator that measures value migration and that can be applied to SMEs that do not have market capitalization information. For this purpose, a questionnaire was developed to be answered by a non–probabilistic sample of SME managers that looks for the driven factors of value migration grouped into different dimensions. The value migration indicator was obtained by adding the scores of the ordinal variables surveyed, and the contributions of each by dimension was also determined. Applying the non–parametric Mann–Whitney test, the most significant variables that affect value migration were identified. Findings indicate that technological advances and the engagement of companies with their environment are fundamental elements for capturing value and should be considered when designing their business model. The proposed index overcomes the limitation of Slywotzky indicator, the only pre–existing analogous indicator, which can only be applied to companies with market capitalization. It is a valuable tool for companies to measure whether they are losing, retaining or gaining value and provides information to improve strategic planning and the decision–making process. In addition, it enables to analyze the business model and its adjustment in relation to changing customer priorities.